Spatiotemporal Trend of Hazardous Waste Sites and Risks in Urban Jakarta, Indonesia - Lestari, Fatma; Zakianis; Muzanni, Adonis; Wibowo, Andrio; Darmawan, Adi; Kurniaputri, Hikmah; Amalia, Khansa Alda; Shaw, Rajib (Sustainability, 2025)
Urban areas are characterized by growing populations and industrial and economic sectors. This leads to trends of increasing hazardous wastes. The aim of this study was to evaluate the trends of hazardous waste risks in several districts in urban Jakarta for the years 2021 and 2022. The results confirmed that, from 2021 to 2022, there were increases in hazardous-waste-producing sites and particular sectors, and decreases in the amount of hazardous waste produced. From 2021 to 2022, the hazardous-waste-producing sectors increased by 55.96%, and the total hazardous waste amount across Jakarta decreased from 644,999.93 tons in 2021 to 521,036.75 tons in 2022. The hazardous-waste-producing sectors were mostly in North and East Jakarta, and there were trends of new hazardous-waste-producing sectors emerging in West and South Jakarta districts from 2021 to 2022. The hazardous-waste-producing sectors were dominated by the manufacturing sectors and emerging healthcare sector. From 2021 to 2022, the hazardous waste trends shifted from industrial to medicinal wastes, and the risks shifted from corrosive, explosive, and toxic to infectious risks. The risk levels of urban Jakarta based on hazardous waste risk scores fall into the medium levels. Based on the spatial statistical analyses, Moran’s I, and LISA, the hazardous waste sites and high amounts of waste in 2021 tended to be clustered in North, East, and West Jakarta, while in 2022, this cluster tended to be dispersed.